IMPLEMENTASI KEBIJAKAN PELARANGAN ALAT TANGKAP CANTRANG DI KABUPATEN REMBANG - M. Faizal Reza Pahlefi; Zainal Hidayat (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
The Policy Implementation on The prohibition of Cantrang net is based on The Regulation Of Maritime and Fisheries Affairs Ministry Number 2 of 2015. The increase of unfriendly eco fishery activities and the decline of national fishery resources are to be the background of this policy. The purpose of this research is to describe the policy implementation on prohibition of cantrang net and to analyze the factors that cause obstacles in the implementation of the policy. The methodology used in this research is qualitative descriptive. The research result appeared that in general, quality of the policy has been going well. The process of rule socialization, The ease access of information and service, the accountability of implementation policy , and the achievement of target group coverage, over all was going well. However, the lack of the government anticipation on the impact of the policy become the main factor that cause obstacles in the policy implementation process. Government needs to provide concrete solutions according to the needs of the target group were affected by the policy through capital aid, nets aid that is as good as Cantrang net, the longer transition period of application and material losses compensation for target group.